Genome-wide identification and expression analysis of the GRAS transcription in eggplant (Solanum melongena L.) - Yang, Ting; Li, Cheng; Zhang, Hui; Wang, Jingyu; Xie, Xiaofang; Wen, Yongxian (Frontiers in Genetics, 2022)
GRAS is plant-specific transcription factor and play important roles in plant growth, development and stress responses. In this study, a total of 48 GRAS genes in eggplant (SmGRASs) genome were identified. These genes distributed on 11 chromosomes unevenly, with amino acid length ranging from 417 to 841 aa. Phylogenetic analysis divided 48 GRAS proteins into 13 subgroups. Gene structure showed that 60.42% (29/48) of SmGRASs have no introns. Collinearity analysis found 9 SmGRAS pairs, and all of them belong to segmental duplication. Cis-acting element predictive analysis found four types of cis-acting elements including light response, growth and development, hormone response and stress response. Expression pattern analysis based on the RNA-seq data of eggplant indicated that SmGRASs were expressed differently in various tissues and respond specifically to cold. In addition, quantitative real-time PCR (qRT-PCR) analysis for 8 selected SmGRASs indicated that three genes (SmGRAS2/32/44) were up-regulated under cold stress. These results provided a theoretical basis for further functional study of GRAS genes in eggplant.